Climate resilience and environmental justice: state of research and implementation in planning practice in Germany and beyond. Issue 2 (1st March 2022) - Greiving, Stefan; Fleischhauer, Mark
Abstract : Climate-change adaptation has become a well-established priority in urban and regional development in Germany since the adoption of the German Adaptation Strategy in 2008. Recently, the socioeconomic aspects and concepts of vulnerability and resilience have received growing attention with regard to climate-change adaptation. This article introduces the TPR special issue on climate resilience and environmental justice. In so doing, it discusses the relationship between climate change and socio-spatial inequalities, and their significance for climate-resilient urban and regional development. Based on this discussion and empirical findings from German practice, as well as the assessment of the policy context and participatory reflection, the article identifies several loose ends in research and practice that need to be connected by further converging concepts and indicators in climate-change and environmental-justice research and policies.